Targeting ADT-Induced Activation of the E3 Ubiquitin Ligase Siah2 to Delay the Occurrence of Castration-Resistant Prostate Cancer - Yan, Tingmang; Zhou, Dapeng; Shi, Youwei; Cui, Di; Jiang, Juntao; Han, Bangmin; Xia, Shujie; Wang, Zhou; Liu, Haitao; Guo, Wenhuan; Jing, Yifeng (Frontiers in Oncology, 2021)
Siah2 is an E3 ubiquitin ligase that targets androgen receptor (AR) and plays an important role in the development of castration-resistant prostate cancer (CRPC). However, the regulation of Siah2 in prostate cancer (PCa) is largely unknown. In this study, we used AR-dependent and -independent cells lines to investigate the cellular roles of AR and androgen deprivation therapy (ADT) on Siah2 protein levels and E3 ligase activity using western blotting and co-immunoprecipitation. We also validated our findings using patient samples taken before and after ADT. Finally, we used xenograft tumor models to test the effects of ADT combined with Vitamin K3 (Vit K3) on tumor growth in vivo. Our results showed that AR stabilizes Siah2 protein by attenuating its self-ubiquitination and auto-degradation, likely by blocking its E3 ubiquitin ligase activity. Conversely, ADT decreased Siah2 protein expression but enhanced its E3 ligase activity in PCa cells. Notably, the findings that ADT decreasing Siah2 protein expression were verified in a series of paired PCa samples from the same patient. Additionally, we found that ADT-induced Siah2 activation could be abolished by Vit K3. Strikingly, ADT combined with Vit K3 treatment delayed the occurrence of CRPC and dramatically inhibited the growth of tumor xenografts compared with ADT treatment alone. AR is an inhibitor of Siah2 in PCa and ADT leads to the continuous activation of Siah2, which may contribute to CRPC. Finally, ADT+Vit K3 may be a potential approach to delay the occurrence of CRPC.